THE MODULE «VIRTUAL ELECTRONIC BOARD» OF DISTANCE LEARNING SYSTEM «KHERSON VIRTUAL UNIVERSITY 2.0» - Kozlovskij, E. O.; Ljakutin, V. V.; Kravtsov, H. M. (Informat͡s︡iĭni tekhnolohiï v osviti, 2010)
Results of structure modeling, construction of learning model and development of program module Whiteboard – a virtual electronic board of distance learning system «Kherson Virtual University» are presented.